VARYING LEVELS OF IMPORTANCE ATTRIBUTED TO MARKETING OUTCOMES FOR THE PURPOSES OF EVALUATIONS OF ORGANIZATIONAL EFFECTIVENESS IN THE LIGHT OF A STUDY INVOLVING COMPANY MANAGERS - Witold Kowal (Polityki Europejskie, Finanse i Marketing)
Organizational evaluations are something obvious. Company effectiveness may be the subject of such an evaluation. Most often, effectiveness is associated with the accomplishment of goals. The development of marketing concepts has demonstrated numerous relationships between the results representing a firm’s principal goals and its marketing outcomes. This paper aims to examine the differences in importance attached to the results of various marketing activities for the purposes of organizational assessment. Therefore, it would seem justified to expect a growing impact of marketing outcomes on the evaluation of organisational effectiveness. The results of the study proved that an increase in the significance attributed to effectiveness as a criterion for organisational evaluation was accompanied by a corresponding increase in the significance attributed to the results representing a company's principal goals. The same tendency could be observed only in respect of small number of marketing outcomes.